Health implications of chronic hepatosplenomegaly in Kenyan school-aged children chronically exposed to malarial infections and Schistosoma mansoni - Wilson, Shona (Oxford University Press, 2010)
Hepatosplenomegaly among school-aged children in sub-Saharan Africa is highly prevalent. Two of the more common aetiological agents of hepatosplenomegaly, namely chronic exposure to malaria and Schistosoma mansoni infection, can result in similar clinical presentation, with the liver and spleen being chronically enlarged and of a firm consistency. Where co-endemic, the two parasites are thought to synergistically exacerbate hepatosplenomegaly. Here, two potential health consequences, i.e. dilation of the portal vein (indicative of increased portal pressure) and stunting of growth, were investigated in a study area where children were chronically exposed to malaria throughout while S. mansoni transmission was geographically restricted. Hepatosplenomegaly was associated with increased portal vein diameters, with enlargement of the spleen rather than the liver being more closely associated with dilation. Dilation of the portal vein was exacerbated by S. mansoni infection in an intensity-dependent manner. The prevalence of growth stunting was not associated with either relative exposure rates to malarial infection or with S. mansoni infection status but was significantly associated with hepatosplenomegaly. Children who presented with hepatosplenomegaly had the lowest height-for-age Z-scores. This study shows that hepatosplenomegaly associated with chronic exposure to malaria and schistosomiasis is not a benign symptom amongst school-aged children but has potential long-term health consequences.